Evaluation of Antimicrobial Activity of Rhinacanthus nasutus (L.) Kurz and Acanthus ilicifolius L. Extracts - Onvimol, Nartlada; Onvimala, Napa; Boohuad, Nattaporn (Journal of Food Health and Bioenvironmental Science, 2023)
The aim of this research was to evaluate the antimicrobial properties of medical plants Rhinacanthus nasutus (L.) Kurz and Acanthus ilicifolius L. that were extracted with water/aqueous (AqER, AqEA) and ethanol (EtER, EtEA). The extracts were tested for activity and evaluated based on the effectiveness against three strains of microorganism: Gram-positive bacteria such as Staphylococcus aureus, Gram-negative bacteria such as Escherichia coli, and fungal such as Candida albicans by using the agar well diffusion and broth dilution method. The extracts from Rhinacanthus nasutus and Acanthus ilicifolius with ethanol showed the effect of inhibiting all microbes. The most effective against Candida albicans with the similar MIC and MFC values of 18.75 and 37.50 mg/mL. Meanwhile, extracts with water of Rhinacanthus nasutus and Acanthus ilicifolius with MIC values of 37.50 and 75 mg/mL and MFC values of 75 and 150 mg/mL, respectively. Conversely, these extracts showed no effect to inhibit Escherichia coli. This could be due to the capabilities of the solvents extractive and using part of the plant. Likewise, a combination of the extracts with ethanol of R. nasutus and A. ilicifolius to evaluate the efficacy of synergistic herbs can be considered from the MIC value. The antimicrobial synergy was evaluated in terms of FIC obtained from multiple-combination bactericidal/fungicidal assays. FICi value was interpreted as synergy only in ethanol extract R. nasutus+A. ilicifolius (EtRA) of 0.26.